Ternary LaNi4.75M0.25 hydrogen storage alloys: Surface segregation, hydrogen sorption and thermodynamic stability. (15th January 2019) - Łodziana, Z.; Dębski, A.; Cios, G.; Budziak, A.
Abstract: Modification of compounds like LaNi5 toward ternary compositions change alloy hydrogen storage properties and influence resistance to hydrogen contamination. Below thermodynamic properties of ternary alloys LaNi4.75 M0.25 are investigated with ab initio methods and synthesized in order to select the composition with hydrogen sorption properties not worse than LaNi5 . The specific volume change, surface segregation energy and change of the hydride formation enthalpy are calculated for 34 elements (M: Ag, Al, Au, B, Bi, Ca, Cd, Cu, Cr, Fe, Ga, Ge, In, Ir, K, Mg, Mn, Mo, Nb, Pb, Pd, Pt, Rh, Ru, Sb, Sn, Ti, V, W, Y, Zn, Zr) substituting Ni. Five ternary compounds are synthesized and analyzed with respect to crystal structure and hydrogen sorption properties. Compounds like LaNi4.75 Ag0.25 . and LaNi4.75 Pb0.25 show favorable stability and H2 sorption thermodynamics. The substituting elements segregating toward the surface are expected to be catalytically active for hydrogen contamination gasses. Graphical abstract: Highlights: Theoretical prediction of thermodynamic properties of 34 ternary LaNi5-x Mx alloys for hydrogen storage. Pressure-concentration isotherms for new nominal LaNi4.75 Ag0.25 Hx, LaNi4.75 Pb0.25 Hx hydrides. Surface segregation in ternary LaNi5-x Mx alloys. Correlation of the volume expansion in ternary LaNi5-x Mx alloys with the atomic radii of Ni substituting elements. The site preference for Ni substitution in LaNi5 .